Battery aluminum-plastic film composite material applied to new energy automobile
By adopting a three-layer structure-designed battery aluminum-plastic film composite, the problems of insufficient mechanical strength, poor barrier performance and unstable heat sealing effect in new energy vehicles are solved, and excellent barrier, mechanical and heat sealing performance is achieved, which significantly improves the service life of the battery and the reliability of the vehicle.
Patent Information
- Application Number
- CN202510056671.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-14
AI Technical Summary
In the complex operating conditions of new energy vehicles, traditional battery aluminum-plastic films have insufficient mechanical strength, poor barrier performance, and unstable heat sealing effect, resulting in battery safety, stability and service life problems.
The battery aluminum-plastic film composite material is designed with a three-layer structure. The outer protective layer is a high-strength aluminum alloy thin plate, the intermediate barrier layer is a multi-layer composite structure with alternating superposition of modified polyvinyl alcohol and ultra-thin metal foil. The inner heat sealing layer is a new thermoplastic elastomer material that is integrated into nano-scale silica particles.
The excellent balance of barrier performance, mechanical strength and heat sealing performance is achieved, which significantly extends the service life of the battery, reduces the risk of failure caused by damage to the battery case, and improves the reliability and safety of the vehicle.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery materials, in particular to a battery aluminum-plastic film composite material applied to new energy vehicles. Background Art
[0002] As the global automotive industry accelerates its transformation towards new energy, power batteries, as core components of new energy vehicles, have received great attention for their safety, stability and service life. Battery aluminum-plastic film, as the outer packaging material of power batteries, plays a key role in protecting the internal battery cells from external environmental erosion and mechanical impact.
[0003] Traditional battery aluminum-plastic films have exposed many shortcomings when facing the complex and changeable operating conditions of new energy vehicles. On the one hand, the mechanical strength of ordinary outer materials is limited, and it is difficult to withstand the frequent vibrations, collisions, and external forces such as stone impacts during vehicle driving, which is prone to damage, thereby threatening the safety of the battery cells inside the battery; on the other hand, the barrier performance of the middle barrier layer is not ideal, and it cannot effectively prevent the long-term penetration of water vapor and oxygen, making the internal chemical system of the battery susceptible to interference, resulting in rapid attenuation of battery capacity and shortened life. In addition, the heat sealing effect of the inner heat sealing layer is unstable, the heat sealing strength is insufficient or the compatibility with the battery cell material is poor, which can easily cause problems such as leakage at the package, aging and cracking, and seriously affect the overall performance and reliability of the battery. Therefore, it is urgent to develop a new battery aluminum-plastic film composite material that can fully meet the stringent requirements of new energy vehicles. Summary of the invention
[0004] The purpose of the present invention is to provide a battery aluminum-plastic film composite material for new energy vehicles. With a unique three-layer structural design and precise control of the material composition and process parameters of each layer, it successfully achieves an excellent balance between barrier properties, mechanical strength and heat sealing properties, and solves the problem of uneven performance of existing battery aluminum-plastic film materials at one stroke.
[0005] The present invention is achieved through the following technical solutions:
[0006] The battery aluminum-plastic film composite material of the present invention is carefully designed from the outside to the inside to include an outer protective layer, a middle barrier layer and an inner heat-sealing layer.
[0007] Outer protective layer:
[0008] High-strength aluminum alloy sheets containing aluminum, magnesium, zinc and trace rare earth elements are used, and the content of rare earth elements is precisely controlled at 0.1%-1% of the total weight of the alloy. The thickness of the outer protective layer is strictly limited to 20-50μm, and its Vickers hardness reaches 80-120HV after professional testing. This unique alloy formula and thickness design give the outer protective layer excellent impact resistance and wear resistance, so that it can effectively resist various external mechanical forces in the complex operating environment of new energy vehicles, providing a rock-solid first protective barrier for the battery.
[0009] Middle barrier layer:
[0010] The structure is a multi-layer composite structure composed of alternating modified polyvinyl alcohol (PVA) film and ultra-thin metal foil. The cross-linking degree of the modified PVA film is finely adjusted to 30%-60%, and the ultra-thin metal foil uses aluminum foil with a purity of not less than 99.5%. The total thickness of the intermediate barrier layer is precisely controlled at 10-30μm. Such a fine structure and parameter setting ensures that the water vapor transmission rate is less than 0.01g / (m 2 d) Oxygen permeability is less than 0.001cm 3 / (m 2 ·d·Pa), creating a highly stable chemical environment inside the battery and greatly extending the battery life.
[0011] Inner heat seal layer:
[0012] A new type of thermoplastic elastomer material incorporating nano-scale silica particles is selected, with the mass of nano-silicon dioxide particles accounting for 2%-8% of the total mass of the thermoplastic elastomer material. The thickness of the inner heat-sealing layer is limited to 10-20μm, the heat-sealing starting temperature is stabilized between 120-150℃, and the heat-sealing strength is guaranteed to be above 30-50N / 15mm. This not only ensures good compatibility with battery electrodes and avoids chemical reactions affecting battery performance, but also achieves a reliable and stable heat-sealing effect, ensuring the sealing and safety of battery packaging.
[0013] As a further improvement of the technical solution of the present invention, the present invention also optimizes the materials of each layer as follows:
[0014] Outer protective layer:
[0015] The alloy composition, by weight percentage, is 85%-95% aluminum, 2%-6% magnesium, 1%-3% zinc, and the rare earth elements are fine-tuned according to actual needs within the above-mentioned limited proportions. Through rigorous composition control, the comprehensive performance of the alloy is optimized to perfectly adapt to the complex and changeable working conditions of new energy vehicles.
[0016] The surface of the aluminum alloy sheet is treated with micro-arc oxidation to form a ceramic film layer with a thickness of 1-3μm. This additional treatment significantly enhances the corrosion resistance and insulation of the outer protective layer, further improving the safety of the battery in complex environments such as high temperature, humidity, acid and alkali.
[0017] Middle barrier layer:
[0018] The number of alternating layers of modified PVA film and ultra-thin metal foil is 3-5, and the layers are tightly bonded through vacuum hot pressing composite process. The thickness of each modified PVA film is 2-6μm, and the thickness of ultra-thin metal foil is 4-8μm. This fine structural design and process coordination can synergistically improve the barrier performance and ensure that the middle barrier layer is impeccable.
[0019] During the preparation process of the modified PVA film, 0.5%-2% of nano-montmorillonite is added. Through intercalation and compounding, the nano-montmorillonite further enhances the barrier properties of the film, reducing the water vapor transmission rate by 10%-20% and the oxygen transmission rate by 15%-25% on the original basis, providing better protection for the battery.
[0020] Inner heat seal layer:
[0021] The new thermoplastic elastomer material used is selected from one or more mixtures of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS) or their modified derivatives, which fully guarantees the flexibility and heat-sealing processing performance of the material and meets the needs of large-scale industrial production.
[0022] During the processing and molding process, an antioxidant with a mass fraction of 0.1%-0.5% is added, and the antioxidant is selected from a mixture of one or more of hindered phenol antioxidants and phosphite antioxidants. This measure effectively prevents the material from aging and degradation under long-term high temperature environment, ensuring that the heat seal layer always maintains stable performance during the long service life of the battery.
[0023] The present invention has the following beneficial effects:
[0024] The battery aluminum-plastic film composite material of the present invention successfully achieves an excellent balance of barrier properties, mechanical strength and heat sealing properties by virtue of its unique three-layer structural design and precise control of the material composition and process parameters of each layer, thus solving the problem of uneven performance of existing battery aluminum-plastic film materials.
[0025] The high-strength aluminum alloy sheet of the outer protective layer combined with the surface micro-arc oxidation treatment provides super physical protection for the battery, effectively resists external mechanical damage, greatly extends the actual service life of the battery, significantly reduces the risk of new energy vehicles causing failures due to damage to the battery casing, and improves the reliability and safety of vehicle operation.
[0026] The multi-layer composite fine structure of the middle barrier layer and the enhanced modification of nano-montmorillonite greatly improve the barrier performance against moisture and oxygen, almost perfectly maintain the stability of the internal chemical environment of the battery, ensure the high consistency and reliability of battery performance, effectively reduce the battery capacity attenuation and safety risks caused by environmental factors, and extend the battery life.
[0027] The new thermoplastic elastomer material of the inner heat-sealing layer combined with antioxidants not only ensures excellent heat-sealing effect, but also improves compatibility with battery electrodes, simplifies the packaging process, improves packaging quality, reduces production costs, and provides solid technical support for large-scale industrial production and commercial promotion of new energy vehicle batteries. DETAILED DESCRIPTION
[0028] The present invention will be described in detail below in conjunction with embodiments and specific examples. The illustrative embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention.
[0029] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, upper end, lower end, top, bottom...) are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture (as shown in the embodiment). If the specific posture changes, the directional indication will also change accordingly.
[0030] In the present invention, unless otherwise clearly defined and limited, the term "connection" should be understood in a broad sense, for example, "connection" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0031] In addition, in the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features; in addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0032] The present invention is described in further detail below.
[0033] A battery aluminum-plastic film composite material used in new energy vehicles, comprising, from the outside to the inside, an outer protective layer, a middle barrier layer and an inner heat-sealing layer, wherein:
[0034] The outer protective layer is a high-strength aluminum alloy sheet containing aluminum, magnesium, zinc and trace rare earth elements, the content of the rare earth elements accounts for 0.1%-1% of the total weight of the alloy, the thickness of the outer protective layer is 20-50 μm, and the Vickers hardness reaches 80-120 HV;
[0035] The intermediate barrier layer is a multilayer composite structure formed by alternating PVA film and ultra-thin metal foil, the crosslinking degree of the modified PVA film is 30%-60%, and the ultra-thin metal foil is an aluminum foil with a purity of not less than 99.5%, and the total thickness of the intermediate barrier layer is between 10-30 μm;
[0036] The inner heat-sealing layer is a new type of thermoplastic elastomer material incorporating nano-scale silicon dioxide particles, the mass of the nano-silicon dioxide particles accounts for 2%-8% of the total mass of the thermoplastic elastomer material, the thickness of the inner heat-sealing layer is 10-20 μm, the heat-sealing starting temperature is between 120-150° C., and the heat-sealing strength is above 30-50N / 15mm.
[0037] Specifically, in the present embodiment, the alloy composition in the outer protective layer is, by weight percentage, 85%-95% aluminum, 2%-6% magnesium, 1%-3% zinc, and the rare earth elements are slightly adjusted within the above-specified proportions.
[0038] Specifically, in this embodiment, the number of alternating layers of modified PVA film and ultra-thin metal foil in the intermediate barrier layer is 3-5, and the layers are tightly bonded through a vacuum hot pressing composite process. The thickness of each layer of modified PVA film is 2-6 μm, and the thickness of the ultra-thin metal foil is 4-8 μm.
[0039] Specifically, in this embodiment, the new thermoplastic elastomer material used in the inner heat-sealing layer is selected from a mixture of one or more of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS) or their modified derivatives.
[0040] Specifically, in this embodiment, a method for preparing a battery aluminum-plastic film composite material for a new energy vehicle comprises the following steps:
[0041] Preparation of outer protective layer:
[0042] The raw materials are accurately weighed according to the predetermined alloy composition ratio, and the temperature is raised to 700-800°C for melting in a vacuum melting furnace with a vacuum degree of not less than 1×10-3Pa, and the refining time is not less than 30 minutes.
[0043] The cast thin plate blank is rolled through multiple passes, with the reduction rate of each pass controlled at 10%-20%, and finally annealed at 300-400°C for 1-2 hours.
[0044] Preparation of intermediate barrier layer:
[0045] The PVA powder is dissolved in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 3-4:1) to prepare a 10%-20% concentration solution, and a cross-linking agent such as glutaraldehyde is added to react at 50-70° C. for 2-4 hours.
[0046] The high-purity aluminum ingot is rolled at room temperature by a multi-roll cold rolling mill at a rolling speed of 10-20m / min to an ultra-thin thickness specification, and then the modified PVA film and the ultra-thin metal foil are compounded by vacuum hot pressing at a hot pressing temperature of 150-200°C, a pressure of 5-10MPa, and a time of 10-20 seconds.
[0047] Inner heat seal layer preparation:
[0048] The thermoplastic elastomer raw material and nano-silicon dioxide particles are mixed in a high-speed mixer at a speed of 800-1200 rpm for 30-60 minutes until they are uniformly dispersed, and melt-blended and extruded into granules at 160-180° C. using a twin-screw extruder with a screw speed of 200-300 rpm.
[0049] The obtained masterbatch is made into an inner heat-sealing layer film at 140-160° C. and a blowing ratio of 2-3 through a blow molding process.
[0050] Composite molding:
[0051] The dry composite process is used to coat the outer protective layer, the middle barrier layer and the inner heat sealing layer with a coating amount of 2-4g / m 2 , composite pressure 0.2-0.4MPa, temperature 50-70℃ conditions.
[0052] Specifically, in this embodiment, the surface of the aluminum alloy sheet of the outer protective layer is treated by micro-arc oxidation to form a ceramic film layer with a thickness of 1-3 μm.
[0053] Specifically, in this embodiment, the modified PVA film of the intermediate barrier layer is added with 0.5%-2% by mass of nano-montmorillonite during the preparation process.
[0054] Specifically, in this embodiment, during the processing and molding process, the new thermoplastic elastomer material of the inner heat-sealing layer is added with an antioxidant with a mass fraction of 0.1%-0.5%, and the antioxidant is selected from a mixture of one or more hindered phenol antioxidants and phosphite antioxidants.
[0055] Specifically, in the embodiment, during the rolling process, the outer protective layer adopts an emulsion lubrication cooling process, the emulsion flow rate is 5-10 L / min, and the emulsion temperature is controlled at 20-30°C.
[0056] Specifically, in the embodiment, the battery aluminum-plastic film composite material after composite molding needs to be subjected to electron beam irradiation treatment, and the irradiation dose is 10-30 kGy.
[0057] The following is a precise preparation method of the battery aluminum-plastic film composite material of the present invention:
[0058] Preparation of outer protective layer:
[0059] First, according to the predetermined alloy composition ratio, use a high-precision electronic scale to accurately weigh the raw materials to ensure that the content error of each element is controlled within a very small range. The raw materials are put into a vacuum melting furnace with a vacuum degree of not less than 1×10-3Pa, and the temperature is raised to 700-800℃ for melting. The refining time is not less than 30 minutes. During this period, the furnace is continuously monitored to ensure sufficient impurities. For example, in an actual preparation, 90kg of high-purity aluminum ingots, 4kg of magnesium ingots, 2kg of zinc ingots, and 1kg of intermediate alloys containing rare earth elements are weighed and put into the melting furnace.
[0060] The cast thin plate blank is rolled in multiple passes, and the reduction rate of each pass is strictly controlled at 10%-20% to ensure the uniformity and mechanical properties of the thin plate. Finally, it is annealed at 300-400℃ for 1-2 hours to eliminate the rolling stress and produce a high-strength aluminum alloy thin plate that meets the thickness and mechanical property requirements. During the rolling process, the emulsion lubrication cooling process is adopted, the emulsion flow is accurately controlled at 5-10L / min, and the emulsion temperature is stably controlled at 20-30℃. For example, in a certain production batch, the emulsion flow is set to 8L / min and the temperature is maintained at 25℃, which effectively improves the surface quality and flatness of the aluminum alloy thin plate and reduces the rolling energy consumption.
[0061] The surface of the aluminum alloy sheet is treated with micro-arc oxidation to form a ceramic film with a thickness of 1-3μm. Taking an outer protective layer used in a new energy vehicle as an example, a ceramic film with a hardness of not less than 1500HV is successfully prepared through micro-arc oxidation equipment in a specific electrolyte system, applying a voltage of 300-500V for a treatment time of 10-20 minutes, which significantly improves corrosion resistance and insulation.
[0062] Preparation of intermediate barrier layer:
[0063] Dissolve the PVA powder in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 3:1-4:1), use a magnetic stirrer to continuously stir, and make a 10%-20% concentration solution. Then add a cross-linking agent such as glutaraldehyde, and react at 50-70°C for 2-4 hours. During this period, the reaction progress is monitored in real time by online monitoring equipment to ensure that the cross-linking modification effect is optimal. For example, in an experimental preparation, 150g of PVA powder was dissolved in a mixed solvent of 750ml of deionized water and 250ml of anhydrous ethanol, 5g of glutaraldehyde was added, and the reaction was carried out at 60°C for 3 hours to obtain a modified PVA solution with excellent performance.
[0064] After the reaction is completed, the film is made into a film by casting and quickly transferred to a constant temperature and humidity oven and dried at 80-100°C for 1-2 hours to remove residual solvent. The film is then biaxially stretched 2-3 times to improve its mechanical properties and barrier properties. A batch of modified PVA film was dried at 90°C for 1.5 hours and biaxially stretched 2.5 times, and the water vapor transmission rate was reduced to 0.005g / (m 2 d) or below.
[0065] High-purity aluminum ingots are rolled at room temperature on a multi-roll cold rolling mill. The rolling speed is precisely controlled at 10-20m / min and rolled to ultra-thin thickness specifications. The modified PVA film and ultra-thin metal foil are then compounded by vacuum hot pressing. The hot pressing temperature is set at 150-200°C, the pressure is controlled at 5-10MPa, and the time is controlled at 10-20 seconds. They are alternately stacked to form an intermediate barrier layer to ensure that each layer fits tightly without defects such as bubbles and delamination. Taking an intermediate barrier layer sample as an example, an aluminum ingot with a purity of 99.8% is selected, and the rolling speed is 15m / min. It is rolled into an ultra-thin metal foil with a thickness of 6μm, which is alternately stacked with 4 layers of modified PVA film (each layer is 4μm thick). After vacuum hot pressing and compounding, the oxygen permeability is as low as 0.0005cm 3 / (m 2 ·d·Pa).
[0066] Inner heat seal layer preparation:
[0067] Thermoplastic elastomer raw materials and nano-silica particles are mixed in a high-speed mixer at a speed of 800-1200rpm for 30-60 minutes in proportion, and the dispersion of particles is monitored in real time by a laser particle size analyzer to ensure uniform dispersion. Then, a twin-screw extruder is used for melt blending and extrusion granulation at 160-180°C, and the screw speed is stabilized at 200-300rpm to produce high-performance masterbatch. For example, 90kg of SBS thermoplastic elastomer raw materials are mixed with 5kg of nano-silica particles, stirred at a speed of 1000rpm in a high-speed mixer for 45 minutes, and a masterbatch with stable quality is obtained after processing by a twin-screw extruder.
[0068] The obtained masterbatch is made into an inner heat-sealing film through a blow molding process at 140-160°C and a blow ratio of 2-3. During the process, the process parameters are adjusted in real time by an online thickness monitor to ensure the uniformity of the film thickness. In a certain production example, the blow molding temperature is set to 150°C and the blow ratio is 2.5. The thickness of the prepared inner heat-sealing film is uniformly controlled at about 15μm, the heat-sealing starting temperature is 135°C, and the heat-sealing strength reaches 40N / 15mm.
[0069] Composite molding:
[0070] The dry composite process is used to coat the outer protective layer, the middle barrier layer and the inner heat sealing layer with a coating amount of 2-4g / m 2 , laminating under the conditions of laminating pressure of 0.2-0.4MPa and temperature of 50-70℃. During the laminating process, high-precision pressure sensors and temperature sensors are used to monitor the laminating parameters in real time to ensure that each layer is tightly combined without defects such as delamination and bubbles, and the final battery aluminum-plastic film composite material is obtained. Taking a batch of products as an example, the glue coating amount is controlled at 3g / m 2 , composite pressure 0.3MPa, temperature 60℃, the prepared composite materials have each layer tightly fitted and excellent performance.
[0071] After composite molding, the battery aluminum-plastic film composite material needs to be irradiated with electron beams, and the irradiation dose is precisely controlled at 10-30kGy. Through irradiation cross-linking, the bonding force between the parts is enhanced, the overall mechanical properties and temperature resistance of the material are improved, the tensile strength is increased by 5%-10%, and the thermal decomposition temperature is increased by 10-20℃. For example, after a certain model of battery aluminum-plastic film composite material was irradiated with 20kGy of electron beam, the tensile strength increased from 200MPa to 210MPa, and the thermal decomposition temperature increased from 300℃ to 320℃.
[0072] Application Scenario
[0073] Urban commuting scenario: In daily urban road driving, new energy vehicles are frequently started and stopped, and the battery pack is constantly subjected to vibration shocks. The battery aluminum-plastic film of the present invention can effectively resist these vibrations by virtue of the high-strength aluminum alloy sheet of the outer protective layer, and prevent the displacement of the internal battery cells or damage to the outer shell caused by long-term vibration. At the same time, the stable barrier performance of the intermediate barrier layer can prevent water vapor and oxygen from invading the battery under the complex temperature and humidity environment of the city, maintain stable battery performance, and ensure that the battery capacity attenuation is effectively controlled when the vehicle is frequently charged and discharged under congested road conditions, ensuring that the driver does not need to worry about the endurance problem frequently and can successfully complete the daily commute.
[0074] High-speed long-distance driving scenario: When new energy vehicles are driving at high speeds, the battery pack faces greater wind resistance and strong impacts caused by bumps on the road. At this time, the outer protective layer of the battery aluminum-plastic film not only relies on its own high strength to resist impact, but the micro-arc oxidation ceramic film layer on its surface can also resist erosion by dust, rain and other erosions carried by high-speed airflow, protecting the battery from damage. After long-term high-speed driving, the battery heats up significantly. The good heat sealing performance and anti-aging properties of the inner heat sealing layer ensure the sealing of the battery package and prevent the package gap caused by thermal expansion and contraction. Combined with the efficient barrier of the middle barrier layer, the battery can still maintain a stable chemical environment under high-temperature and high-speed conditions, providing reliable power support for long-distance travel, and the driver does not need to stop and rest frequently due to fluctuations in battery performance.
[0075] Application in extreme climate areas: In the cold northern winter or the hot and humid southern summer, new energy vehicle batteries face severe tests. At extremely low temperatures, the brittleness of battery materials increases. The outer protective layer of the battery aluminum-plastic film of the present invention can buffer the impact of external cold and prevent the battery shell from cracking; the middle barrier layer has a nearly perfect ability to block water vapor and oxygen, eliminating the risk of battery short circuit caused by water vapor condensation at low temperatures. In the hot and humid south, its barrier properties also ensure the stability of the internal chemical system of the battery, delay battery aging, and enable new energy vehicles to adapt to the use requirements of different climate zones, expanding the application area of the vehicle. Whether it is the icy and snowy Northeast or the hot and humid Hainan, the vehicle can operate normally.
[0076] Application in high-performance sports cars: For new energy sports cars that pursue extreme performance, powerful power output means that the battery needs to withstand higher instantaneous current shocks and more intense acceleration and braking caused by inertia. The battery aluminum-plastic film composite material of the present invention has various layers that work together. The outer high-strength protective layer provides mechanical protection, the middle barrier layer maintains the chemical stability of the battery, and the inner heat-sealing layer ensures reliable packaging, which meets the ultra-high requirements of sports cars for battery safety and stability, and ensures that the battery is always in the best working state during the racetrack or high-speed passionate driving, providing a solid backing for the ultimate speed and control experience.
[0077] The battery aluminum-plastic film composite material obtained through the above careful design and strict preparation process has undergone a series of professional and rigorous performance tests. In terms of barrier performance, the water vapor transmission rate is less than 0.01g / (m 2 d) Oxygen permeability is less than 0.001cm 3 / (m 2 ·d·Pa); in terms of mechanical strength, the tensile strength reaches more than 210MPa, the heat sealing performance is good, and the heat sealing strength is above 30-50N / 15mm, which fully meets the use requirements of new energy vehicle batteries under various harsh working conditions and provides strong support for the development of the new energy vehicle industry.
[0078] Compared with the prior art, the present invention has the following beneficial effects:
[0079] The battery aluminum-plastic film composite material of the present invention successfully achieves an excellent balance of barrier properties, mechanical strength and heat sealing properties by virtue of its unique three-layer structural design and precise control of the material composition and process parameters of each layer, thus solving the problem of uneven performance of existing battery aluminum-plastic film materials.
[0080] The high-strength aluminum alloy sheet of the outer protective layer combined with the surface micro-arc oxidation treatment provides super physical protection for the battery, effectively resists external mechanical damage, greatly extends the actual service life of the battery, significantly reduces the risk of new energy vehicles causing failures due to damage to the battery casing, and improves the reliability and safety of vehicle operation.
[0081] The multi-layer composite fine structure of the middle barrier layer and the enhanced modification of nano-montmorillonite greatly improve the barrier performance against moisture and oxygen, almost perfectly maintain the stability of the internal chemical environment of the battery, ensure the high consistency and reliability of battery performance, effectively reduce the battery capacity attenuation and safety risks caused by environmental factors, and extend the battery life.
[0082] The new thermoplastic elastomer material of the inner heat-sealing layer combined with antioxidants not only ensures excellent heat-sealing effect, but also improves compatibility with battery electrodes, simplifies the packaging process, improves packaging quality, reduces production costs, and provides solid technical support for large-scale industrial production and commercial promotion of new energy vehicle batteries.
[0083] The technical solutions provided by the embodiments of the present invention are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the embodiments of the present invention. The description of the above embodiments is only applicable to help understand the principles of the embodiments of the present invention. At the same time, for those skilled in the art, according to the embodiments of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A battery aluminum-plastic film composite material used in new energy vehicles, characterized in that: From the outside to the inside, it includes an outer protective layer, a middle barrier layer and an inner heat-sealing layer, among which: The outer protective layer is a high-strength aluminum alloy sheet containing aluminum, magnesium, zinc and trace rare earth elements, the content of the rare earth elements accounts for 0.1%-1% of the total weight of the alloy, the thickness of the outer protective layer is 20-50 μm, and the Vickers hardness reaches 80-120 HV; The intermediate barrier layer is a multilayer composite structure formed by alternating PVA film and ultra-thin metal foil, the crosslinking degree of the modified PVA film is 30%-60%, and the ultra-thin metal foil is an aluminum foil with a purity of not less than 99.5%, and the total thickness of the intermediate barrier layer is 10-30 μm; The inner heat-sealing layer is a new type of thermoplastic elastomer material incorporating nano-scale silicon dioxide particles, the mass of the nano-silicon dioxide particles accounts for 2%-8% of the total mass of the thermoplastic elastomer material, the thickness of the inner heat-sealing layer is 10-20 μm, the heat-sealing starting temperature is 120-150° C., and the heat-sealing strength is 30-50 N / 15 mm.
2. The battery aluminum-plastic film composite material for new energy vehicles according to claim 1, characterized in that: The alloy components in the outer protective layer are calculated by weight percentage, wherein the aluminum content is 85%-95%, the magnesium content is 2%-6%, and the zinc content is 1%-3%.
3. The battery aluminum-plastic film composite material for new energy vehicles according to claim 1, characterized in that: The number of alternating layers of modified PVA film and ultra-thin metal foil in the inter-barrier layer is 3-5, and the layers are tightly bonded by a vacuum hot pressing composite process. The thickness of each modified PVA film is 2-6 μm, and the thickness of the ultra-thin metal foil is 4-8 μm.
4. The battery aluminum-plastic film composite material for new energy vehicles according to claim 1, characterized in that: The novel thermoplastic elastomer material used in the inner heat-sealing layer is selected from a mixture of one or more of styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer or their modified derivatives.
5. The battery aluminum-plastic film composite material for new energy vehicles according to claim 1, characterized in that: The surface of the aluminum alloy sheet of the outer protective layer is treated by micro-arc oxidation to form a ceramic film layer with a thickness of 1-3 μm.
6. The battery aluminum-plastic film composite material for new energy vehicles according to claim 1, characterized in that: The modified PVA film of the intermediate barrier layer is added with 0.5%-2% of nano-montmorillonite by mass during the preparation process.
7. The battery aluminum-plastic film composite material for new energy vehicles according to claim 1, characterized in that: During the processing and molding process, the novel thermoplastic elastomer material of the inner heat-sealing layer is added with an antioxidant with a mass fraction of 0.1%-0.5%, and the antioxidant is selected from a mixture of one or more hindered phenol antioxidants and phosphite antioxidants.
8. A method for preparing the battery aluminum-plastic film composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step S1, preparation of outer protective layer: The raw materials are accurately weighed according to the predetermined alloy composition ratio, and the temperature is raised to 700-800℃ for melting in a vacuum melting furnace with a vacuum degree of not less than 1×10-3Pa, and the refining time is not less than 30 minutes; The cast thin plate blank is rolled in multiple passes, with the reduction rate of each pass controlled at 10%-20%, and finally annealed at 300-400°C for 1-2 hours; Step S2: Preparation of intermediate barrier layer: Dissolve PVA powder in a mixed solvent of deionized water and anhydrous ethanol (volume ratio 3-4:1) to prepare a 10%-20% concentration solution, add a cross-linking agent such as glutaraldehyde and react at 50-70°C for 2-4 hours; The high-purity aluminum ingot is rolled at room temperature by a multi-roll cold rolling mill at a rolling speed of 10-20m / min to an ultra-thin thickness specification, and then the modified PVA film and the ultra-thin metal foil are compounded by vacuum hot pressing at a temperature of 150-200°C, a pressure of 5-10MPa, and a time of 10-20 seconds; Step S3: Preparation of inner heat-sealing layer: The thermoplastic elastomer raw material and the nano-silicon dioxide particles are mixed in a high-speed mixer at a speed of 800-1200 rpm for 30-60 minutes until they are uniformly dispersed, and melt-blended and extruded into granules at 160-180° C. using a twin-screw extruder with a screw speed of 200-300 rpm; The obtained masterbatch is made into an inner heat-sealing layer film by a blow molding process at 140-160°C and a blow ratio of 2-3; Step S14: composite molding: The dry composite process is used to coat the outer protective layer, the middle barrier layer and the inner heat sealing layer with a coating amount of 2-4g / m 2 , composite pressure 0.2-0.4MPa, temperature 50-70℃ conditions.
9. The preparation method according to claim 8, wherein during the rolling process of the outer protective layer, an emulsion lubrication cooling process is adopted, the emulsion flow rate is 5-10 L / min, and the emulsion temperature is controlled at 20-30°C.
10. The preparation method according to claim 8, wherein the battery aluminum-plastic film composite material after composite molding needs to be subjected to electron beam irradiation treatment, and the irradiation dose is 10-30 kGy.
Citation Information
Patent Citations
Polymer lithium ion battery core outer package forming material
CN102431239A
Environment-friendly aluminum plastic film for lithium battery
CN107644952A
Preparation method and application of micro-arc oxidation aluminum foil
CN114395783A
A complex film is moulded to soft alclad of power battery that is used for liquid cooling type power car
CN206884327U